Apoptosis and cell proliferation in the epithelia of the esophagus and intestine of Alburnus tarichi Güldenstädt, 1814 (Cyprinidae) during migration from highly alkaline and brackish water to fresh water. Issue 1 (1st January 2019) - Ceylan, S.; Kaptaner, B.
Abstract: In this study, cellular turnover in the epithelia of the esophagus and intestine of the anadromous Lake Van fish ( Alburnus tarichi ) that migrated from the highly alkaline and brackish water of Lake Van to fresh water were investigated by apoptosis and cell proliferation. Toward this aim, fish were collected from or near the entrance to Lake Van, and upstream in a freshwater stream (Karasu). The tissues were subjected to terminal deoxynucleotidyl transferase nick end labeling and proliferating cell nuclear antigen stainings for the detection of apoptosis or cell proliferation, and were then quantified. In the esophagus epithelium, the apoptotic index (AI) displayed no differences between fish from the lake and those from the freshwater stream. The AI increased significantly at the anterior or mid-intestine epithelia and throughout the intestine epithelium, whereas it remained unchanged in the posterior intestine epithelium of fish from both upstream and at the entrance of the freshwater stream. In the esophagus epithelium, the proliferation index (PI) values decreased gradually in fish from the freshwater stream. The PI increased significantly in the anterior intestine epithelium or throughout the intestinal epithelium of fish collected from the entrance of the stream; however, it did not change along the intestinal epithelium of fish collected upstream in the freshwater stream. It was determined that cellular changes occurred in the esophageal and intestinal epithelium of Lake Van fish during freshwater acclimation.